Yesus Kristus Figur Pemimpin Teladan dan Pelayan - Seran, Yanuarius (JURNAL PROPHETA, 2021)
This article describes leadership as a behavior that influences an individual orgroup of people to work towards achieving goals according to a vision that has been settogether. A leader is a person who has a special ability and aptitude to lead andinfluence members or subordinates to work hard to achieve goals. It changes thebehavior of followers in order to achieve higher performance. He is a visionary, capableof deciding and anticipating the turmoil of any future changes. He became a good andstrong leader, so that subordinates could be exemplary. His words and deeds are in line. He was a brave man who opposed old and obsolete thoughts, and was constantlyexperimenting with new and constructive ideas for the betterment of the institution. Atrue leader will step into the realm of practicality to serve. So the role of a servant leaderprioritizes service. Power and office are used to serve. He practiced the example ofJesus Christ in terms of patience, humility, charity and forgiveness. He is the figure ofChrist who comes to serve, not to be served.